STATISTICAL LEARNING DIFFICULTIES ANALYSIS IN THE ERA OF PANDEMIC COVID-19 IN GUIDANCE AND COUNSELING COLLEGE STUDENTS - Meilla Dwi Nurmala; Stevany Afrizal; Meitami Sofiyanti (Universitas Sultan Ageng Tirtayasa, 2021)
COVID-19 is a virus that spreads around the world. Indonesia is one ofthe affected countries. Everyone has only experienced the current conditions andsituations, so that good adaptations and adjustments are needed in all aspects,including learning. Teachers implement online learning methods to students tominimize the risk of spreading the COVID-19. This research was done with aquantitative description method. The results showed that students' learningdifficulties when learning at home online were inadequate facilities and internetnetworks, insufficient understanding of certain subjects, a learning atmosphere athome that was less conducive to the analysis of students' learning difficultiescarrying out learning online COVID-19 pandemic period. This study aims to obtaininformation about the problems experienced by students in carrying out onlinestatistics learning during the COVID-19 pandemic.Keywords: Online Statistics Learning, COVID-19 Pandemic, LearningDifficulties